The European landscape convention challenges of participation - Jones, Michael; SpringerLink (Online service). (Dordrecht Springer Netherlands Imprint: Springer, 2011)
This important and insightful book provides, for the first time, a broad presentation of ongoing research into public participation in landscape conservation, management and planning, following the 2000 European Landscape Convention which came into force in 2004. The book examines both the theory of participation and what lessons can be learnt from specific European examples. It explores in what manner and to what extent the provisions for participation in the European Landscape Convention have been followed up and implemented. It also presents and compares different experiences of participation in selected countries from northern, southern, eastern and western Europe, and provides a critical examination of public participation in practice. However, while the book{u2019}s focus is necessarily on Europe, many of the conclusions drawn are of global relevance. The book provides a valuable reference for researchers and advanced students in landscape policies and management, as well as for professionals and others interested in land-use planning and environmental management.
Preface -- Contributing authors -- Introduction -- The issue of public participation in the European Landscape Convention, Michael Jones and Marie Stenseke -- Part I: Implementing participation -- European landscape and participation rhetoric or reality, Michael Jones -- The Dutch approach: Public participation and the role of NGOs and local authorities in the protection, management and development of cultural landscapes in the Netherlands, Henk Baas, Bert Groenewoudt, and Edwin Raap -- The participatory dimension in nature conservation processes: Examples of ideology and practice from Norway, Karoline Daugstad -- The implementation of the European Landscape Convention in Poland; Anna Majchrowska -- 6. Landscape regulation in regional territorial planning: A view from Spain; Berezi Elorrieta and Dolores Sánchez-Aguilera -- 7. In search of the Greek landscape: A cultural geography, Theano S. Terkenli -- Part II: Participatory methods and case studies -- 8. Landscape in participatory processes: Tools for stimulating debate on landscape issues. A conceptual and methodological reflection from research-action projects in France, Yves Michelin, Thierry Joliveau, and Claire Planchat-Héry -- 9. The Prospective Vision: Integrating the farmers? point of view into French and Belgian local planning; Claire Planchat-Héry -- 10. Landscape Quality Objectives for remote rural landscapes in Portugal: Addressing experts and stakeholders perspectives on future developments; Isabel Loupa Ramos -- 11. Landscape perception through participation: Developing new tools for landscape analysis in local planning processes in Norway; Morten Clemetsen, Erling Krogh, and Kine Halvorsen Thorén -- 12. Participation within the landscape of the River Dart Catchment, Devon, England; Neil Spencer -- 13. Regional Landscape Strategies and public participation: Towards implementing the European Landscape Convention in Sweden; Anders Larsson, Anna Peterson, Elinor Bjärnborg, Christine Haaland, and Mats Gyllin -- 14. The role of information, knowledge and acceptance during landowner participation in the Natura 2000 designations: The cases of Otepää and Kõnnumaa, Estonia; Monika Su?kevi?s and Mart Külvik -- Conclusion -- 15. Benefits, difficulties and challenges of participation under the European Landscape Convention; Marie Stenseke and Michael Jones -- Index.
Electronic reproduction.
Keywords: Landscape protection -- Law and legislation -- European Union countries; Landscape protection -- Government policy -- European Union countries; Landscape protection -- European Union countries -- Case studies; Landscape protection -- European Union countries -- Citizen participation -- Case studies; Electronic books